Short-term effect of adding nitrogen in forest soil of an urban rainforest - Moraes Nascimento, Bruno; Vieira Cesário, Fernando; de Aragão Rodrigues, Renato; de Carvalho Balieiro, Fabiano; Silva Wanderley, Henderson (Sustainability in Debate, 2020)
The deposition of atmospheric nitrogen has been increased in urban forest ecosystems, yet it is not clear how this increase affects soil respiration in the short term. The soil respiration could contribute to CO2 flux to the atmosphere; therefore, it is essential to understand how nitrogen addition affects soil respiration and its autotrophic and heterotrophic compartments. We established a randomized block experiment to investigate the effects of adding 2.5 kg ha-1 (which corresponds to ~ 40% of the total annual deposition) in soil respiration during five days in an urban tropical forest. The CO2 flux of the autotrophic and heterotrophic compartments was individualized and measured using an infrared gas analyzer (IRGA). Two measurements per day (9-11 and 21-23 hours) were assessed for five consecutive days. Days and nights show no difference in CO2 flux among all compartments. The heterotrophic respiration was strong negatively affected by nitrogen addition, about 34%. Autotrophic respiration was positively impacted by nitrogen addition, but no significant differences were found. Heterotrophic respiration is the primary source of CO2 from the forest soil.